The Effect of E-leaflet Education on Red Onion Administration to Improve Mothers' Knowledge About Reducing Fever After DPT Immunization: PENGARUH EDUKASI E-LEAFLET PEMBERIAN BAWANG MERAH TERHADAP PENINGKATAN PENGETAHUAN IBU TENTANG PENURUNAN DEMAM PASCA IMUNISASI DPT - Sakinah, Innama (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Fever is a normal response of the body to infection or a form of resistance in the body in adjusting antibodies due to immunization. Fever can be a sign of the onset of infection, but fever can also be caused by metabolic disorders and other causes. Red onion (Allium cepa varietas ascalonicum) can be used as a fever reducer for infants and toddlers with fever. The content of organic sulfur compounds, or Allylcysteine Sulfoxide (Alliin). Many parents are still unaware of the benefits of red onions for reducing fever in children. Therefore, the researchers aimed to determine the effect of providing e-leaflet education on the administration of red onions on increasing mothers' knowledge about reducing fever after DPT immunization. Methods: The method used was a pre-experiment, one group pre-test post-test. The sample size was 30 respondents. The results of the study showed that the respondents' knowledge before receiving education through the e-leaflet on the use of shallots was still lacking at 63.4%. Results: Respondents' knowledge after receiving e-leaflet education on the use of shallots was 90%. There was an effect of e-leaflet education on the use of shallots on increasing mothers' knowledge about reducing fever after DPT immunization, with a Sig value of 0.000.) Conclusions: There is an effect of e-leaflet education on giving red onions to increase mothers' knowledge about reducing fever after DPT immunization.